Criterion validity, reliability, and usefulness of a judo-specific maximal aerobic power test - Shiroma, S. A.; Julio, U. F.; Franchini, E. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To evaluate criterion validity, reliability, and usefulness of a test to measure maximal aerobic power using judo-specific movements (uchi-komi test [UKtest]). Methods: A total of 12 judokas performed 5 graded exercise tests (GETs) in 4 sessions. In sessions 1 and 2, upper-body (UBtest), lower-body (LBtest), and familiarization UKtest were performed. GETs were randomly performed and separated by at least 48 h. In sessions 3 and 4, test and retest UKtest were performed (7 d apart). For all GETs, peak oxygen consumption (VO2 peak ), maximal heart rate (HRmax), peak blood lactate concentration [Lapeak], maximal aerobic intensity, and rating of perceived exertion (RPE) were determined. Another group of 12 judokas performed the UKtest and 1 confirmation test (20 min after the UKtest) at 105 % of maximal aerobic speed until exhaustion to confirm whether maximal responses were achieved. Results: VO2 peak did not differ (P > .05) between UKtest (46.04 [5.34] mL/kg·min) and LBtest (44.78 [5.98]mL/kg·min), but it was higher (P < .05) than UBtest (37.03 [7.16] mL/kg·min). Total duration (551 [60] s) and [Lapeak] (7.10 [1.76] mmol/L) in the UKtest were different (P < .05) from UBtest (416 [47] s, 9.93 [2.15] mmol/L, respectively) and LBtest (433 [54] s, 10.29 [2.23] mmol/L, respectively). Very large relationships between VO2 peak in UKtest with UBtest (r = .78; P = .003) and LBtest (r = .87; P < .001) were found. Maximal values were achieved for the UKtest VO2 peak , HRmax, [Lapeak], RPE, and maximal aerobic speed, with no difference between test and retest (P > .05). In addition, very large intraclass correlation coefficients (ICC) for VO2 peak (ICC = .86), HRmax (ICC = .90), and maximal aerobic speed (ICC = .81) were found. Conclusion: The UKtest can be considered a valid, reliable, and useful test to measure maximal aerobic power using judo-specific movements.